The inability to transfer classroom learning to clinical nursing practice: a learning problem and its remedial plan. - Wong J (Journal of Advanced Nursing (Wiley-Blackwell), 1979)
The inability to transfer classroom knowledge to clinical nursing practice is a common learning problem encountered by many nursing students. Manifestations of this problem may involve both the academic performance and personal development of the students: inability to solve problems in nursing situations; inflexibility and rigidity in the exercise of nursing care; fragmentation of nursing care; and apathy towards clinical practice. Because of the seriousness of this learning problem, a plan must be formulated to rectify it. This plan is developed with major emphasis on the teaching process, the student and the curriculum. One of the important roles of a teacher is to help students understand many widely useful relationships, principles or generalizations. In order to enhance transfer, nursing students must be given ample opportunities to apply the learned principles in a variety of nursing situations. Learning is a self-active process; an ideal transfer demands the students' conscious realization that transfer is possible. Students need to be committed to the belief that particular facts in the classroom study are pertinent in other situations. To promote transfer, the curriculum must be designed in such a way so that it has transfer value in terms of the students' goals and purposes. Furthermore, proper sequence of curricular activities